Constraints Influencing Adoption of Solar Technologies Among Farmers - Kumbhare, Narayan Vithoba; C Vaishnavi; R N Padaria; Sitaram Bishnoi; Satish D Lande; Kanchan Sinha; Pushpendra Yadav; Prashanth B (The Indian Journal of Agricultural Sciences, 2026)
Solar photovoltaic technologies offer a sustainable alternative to conventional energy sources for Indian agriculture; however, their adoption at farm level remains limited. The present study analyzed the constraints influencing adoption and non-adoption of solar technologies among farmers in Haryana and Maharashtra. A total sample of 480 farmers, comprising 240 solar technology adopters and 240 non-adopters, were selected using a multistage sampling. Constraints were identified through literature review, field interactions and classified into technical, financial, personal, and institutional categories. The Preference Selection Index (PSI) method was employed to prioritize the perceived severity of constraints. The results indicated that among adopters, post-installation service limitations, non-availability of spare parts, high initial investment, limited duration of subsidy support constituted the most severe barriers. Among non-adopters, high initial investment, inadequate subsidy support, fear of technology failure, and procedural complexity in accessing government incentives emerged as the dominant constraints. The study highlights the need for strengthening decentralized service infrastructure, simplifying administrative procedures, improving access to affordable credit, and reinforcing extension activities through training and demonstrations to accelerate the diffusion of solar technologies to sustainable and climate-resilient agricultural development in India.